2001
DOI: 10.2105/ajph.91.7.1107
|View full text |Cite
|
Sign up to set email alerts
|

Remission from drug abuse over a 25-year period: patterns of remission and treatment use

Abstract: A B S T R A C TObjectives. Using an epidemiologically obtained sample, we examined patterns of illicit drug use, abuse, and remission over a 25-year period and recent treatment use.Methods. The surviving members of the cohort (n = 841), previously surveyed in 1972 and 1974, comprised 3 subsamples of Vietnam War enlisted men and civilian controls. Retrospectively obtained year-to-year measures from the 1996-1997 survey included use and remission of sedatives, stimulants, marijuana, cocaine, and opiates, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…However, the odds of CUD relapse found in our study are much lower than those reported in studies of clinical samples (Catalano et al, 1990; Haney et al, 2010; Perkonigg et al, 2008; Price et al, 2001; Stephens et al, 1994a, 1994b; Witkiewitz and Marlatt, 2004), possibly due to lower average severity of CUD, less psychiatric comorbidity and health issues (Arendt et al, 2007a; Chen et al, 2011), and less exposure to high-risk environments (Benowitz, 2008; Lopez-Quintero et al, 2011; Piasecki, 2006), among community rather than clinical samples. However, exact comparisons with previous findings are difficult because of the different definitions of relapse, follow-up periods and specific characteristics of the samples included across studies (Okuda et al, 2010).…”
Section: Discussioncontrasting
confidence: 93%
“…However, the odds of CUD relapse found in our study are much lower than those reported in studies of clinical samples (Catalano et al, 1990; Haney et al, 2010; Perkonigg et al, 2008; Price et al, 2001; Stephens et al, 1994a, 1994b; Witkiewitz and Marlatt, 2004), possibly due to lower average severity of CUD, less psychiatric comorbidity and health issues (Arendt et al, 2007a; Chen et al, 2011), and less exposure to high-risk environments (Benowitz, 2008; Lopez-Quintero et al, 2011; Piasecki, 2006), among community rather than clinical samples. However, exact comparisons with previous findings are difficult because of the different definitions of relapse, follow-up periods and specific characteristics of the samples included across studies (Okuda et al, 2010).…”
Section: Discussioncontrasting
confidence: 93%
“…Assessment of the potential gender differences in the association of MDE comorbidity with treatment barriers has important clinical implications for identifying interventions aimed at improving treatment access since a small number of individuals with SUD ever enter treatment for their conditions (Cohen et al, 2007; Price et al, 2001). Identifying appropriate targets for improving acceptability of and access to these treatments is a first step to increase service utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Army servicemen (pay grades E1–E9), who had positive urine tests (drug positive status at baseline) for opiates, amphetamines, or barbiturates at the time of their departure from Vietnam in September 1971, comprised half of the original veteran sample; the other half of veterans were drawn from the entire roster of September 1971 returnees (drug-negative status). Further details are described elsewhere (Robins 1974; Robins and Helzer, 1975; Price et al, 2001). All aspects of the series of follow-up studies involving this cohort were approved by the appropriate Institutional Review Boards.…”
Section: Methodsmentioning
confidence: 99%